2022
DOI: 10.3389/fmars.2022.831286
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Biomarker Patterns Reflect Nutritional Strategies of Seep-Dwelling Bivalves From the South China Sea

Abstract: Invertebrates living at methane seeps such as mussels and clams gain nutrition through symbiosis with chemosynthetic, chiefly methanotrophic and thiotrophic bacteria. Lipid biomarkers, including their compound-specific carbon stable isotope compositions, extracted from the host tissues are predestined for deciphering the various sources of diets and the associations among varying environments, endosymbionts, and hosts. Here, we investigated lipid inventories of soft tissues of two bathymodiolin mussel species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 78 publications
(140 reference statements)
0
6
0
Order By: Relevance
“…However, few DEGs were detected between the MS and MA groups (Figure 2c), indicating that the effect of symbiont loss on the mussel transcriptome after long-term laboratory maintenance was much higher than the effect of the difference in abundance of symbionts between the two groups. In addition, despite their ability to filter-feed on organic particulate matter as a supplement of nutrients (Piquet et al, 2022), deep-sea mussels living in natural environments derived the majority of nutrients from their endosymbionts (Guan et al, 2022). In our experiments, mussels were kept unfed under laboratory conditions, and the nutrients supplied by filtration were limited.…”
Section: Metabolic Shift After Symbiont Depletion In Long-term Mainte...mentioning
confidence: 99%
“…However, few DEGs were detected between the MS and MA groups (Figure 2c), indicating that the effect of symbiont loss on the mussel transcriptome after long-term laboratory maintenance was much higher than the effect of the difference in abundance of symbionts between the two groups. In addition, despite their ability to filter-feed on organic particulate matter as a supplement of nutrients (Piquet et al, 2022), deep-sea mussels living in natural environments derived the majority of nutrients from their endosymbionts (Guan et al, 2022). In our experiments, mussels were kept unfed under laboratory conditions, and the nutrients supplied by filtration were limited.…”
Section: Metabolic Shift After Symbiont Depletion In Long-term Mainte...mentioning
confidence: 99%
“…In this seep area, bathymodioline mussel Gigantidas haimaensis Xu et al, 2019, and siboglinid tubeworms Paraescarpia echinospica Southward et al, 2002(Sun et al, 2021 and Sclerolinum annulatum Xu et al, 2022 form huge colonies on the sea bed. Other low-density populations of bivalves were also reported in this area, including Gigantidas platifrons Hashimoto & Okutani, 1994, "Bathymodiolus" aduloides Hashimoto and Okutani, 1994, Nypamodiolus samadiae Lin et al, 2022, and other undetermined species of Malletia and Acharax (Xu et al, 2019;Guan et al, 2022;Ke et al, 2022). These siboglinid and bivalve species are endosymbiotic with chemosynthetic bacteria in their trophosome and gill epithelial cells, respectively, to provide energy and materials for the holobiont (Ip et al, 2021;Sun et al, 2021;Lin et al, 2023).…”
Section: Discussionmentioning
confidence: 76%
“…Among the proteases, cathepsins were thought to be evolutionary conserved molecular tools that host utilized to control the residence of their symbiont microbes 66 . They were also highly expressed in symbiotic tissue of other deep-sea chemosynthetic animals, such as vesicomyid clams and vestimen-tiferan tubeworms 6769 . Bacteriocytes also expressed genes encoding cellular vesicle transports (kinesins, Bpl_scaf_14819-0.11, Bpl_scaf_54265-1.13, and Bpl_scaf_4784-1.40) 53 , potential amino acid transporter 57 (Bpl_scaf_36159-5.5), and genes involved in intracellular vesicle transport, such as the FYVE and coiled-coil domain-containing protein 1 58 (Bpl_scaf_33726-5.7).…”
Section: Resultsmentioning
confidence: 99%
“…The symbiont of G. platifrons belongs to type I methanotrophy, of which the core metabolic function is linked with the development of intracytoplasmic membranes leading to a high lipid/biomass content 70,71 . Recent lipid biomarker analyses showed that the gill of G. platifrons contains a high amount of bacterial lipids, which are directly utilised by the host to synthesise most of its lipid contents 67 . Downstream of the bacteriocyte’s metabolic cascade, genes encoding proteins that may be involved in fatty acid/lipid metabolism, such as perilipin2 (Bpl_scaf_27158-3.8), which is the critical protein to form intracellular lipid droplets 72 , and a variety of fatty acid metabolism enzymes (acetyl carboxylase 2, Bpl_scaf_55250-5.11 73 ; fatty acid desaturase 1-like isoform X1, Bpl_scaf_35916-0.6 74,75 ; long-chain fatty acid-ligase ACSBG2-like isoform X1, Bpl_scaf_28862-1.5 76,77 ), were up-regulated, suggesting that the fatty acid could be a major form of nutrients passing from the symbiont to the host mussel.…”
Section: Resultsmentioning
confidence: 99%